Characteristics and Risk Factors of Diabetic Retinopathy Patients in West Java, Indonesia (Majalah Kedokteran Bandung, 2024)
Diabetic retinopathy (DR) is the major microvascular complication of diabetes mellitus (DM) and responsible as the leading cause of vision loss among working-age adults. With the estimated DM cases reaching 578 million in 2030, public health systems are faced with challenges of increasing costs of implementation and maintenance of DR screening program in people with DM. This study aimed to describe characteristics and risk factors of DR among patients of a Primary Health Care Center in West Java, Indonesia. This was a cross-sectional study during the period of March 2021 until June 2022 on 1,080 participants. Among these participants with DM, 28.89% (25.16–33.12% [95% CI]) were classified to have DR. A total of 32.69% (28.14–36.71 [95% CI]) participants with DR had vision threatening DR (VTDR). The prevalence of DR in this study was higher in women (77.23%) with a mean age of 57.26 ± 9.17 and duration of DM of â‰¥5-years (56.01%), blood glucose level
Keywords: Diabetic retinopathy; public health; screening program